2012
DOI: 10.1002/term.555
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-sintered 3D printed tricalcium phosphate scaffolds for bone tissue engineering

Abstract: We report here the fabrication of three dimensional (3D) interconnected macro porous tricalcium phosphate (TCP) scaffolds with controlled internal architecture by direct 3D printing (3DP), and high mechanical strength by microwave sintering. TCP scaffolds with 27%, 35% and 41% designed macro porosity having pore sizes of 500 μm, 750 μm, and 1000 μm, respectively, have been fabricated via direct 3DP. These scaffolds are then sintered at 1150 °C and 1250 °C in conventional electric muffle furnace as well as micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
238
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(247 citation statements)
references
References 39 publications
9
238
0
Order By: Relevance
“…Composite materials such as combinations of ceramic (TCP), BioGlass, or polymers (natural polymers like collagen) have also been studied for use in 3DP. Composites can be formed either during printing using a polymeric binder with ceramic powder 31 or by initially starting with a ceramic / polymer powder blend 32 and an acid binder. However, powder and binder materials need to be selected with care as free radical initiators after printing can compromise biocompatibility.…”
Section: Jariwala Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Composite materials such as combinations of ceramic (TCP), BioGlass, or polymers (natural polymers like collagen) have also been studied for use in 3DP. Composites can be formed either during printing using a polymeric binder with ceramic powder 31 or by initially starting with a ceramic / polymer powder blend 32 and an acid binder. However, powder and binder materials need to be selected with care as free radical initiators after printing can compromise biocompatibility.…”
Section: Jariwala Et Almentioning
confidence: 99%
“…Poor mechanical properties can render the ceramic 3DP scaffolds unsuitable for high -loadbearing applications. 3DP HA scaffolds impregnated with bis -GMA 43 and TCPsintered scaffolds 31 were shown to improve mechanical properties. A 10 -fold increase in compression strength (76 MPa) of 3DP TCP and tetra CaP (TTCP) scaffolds has been reported by Khalyfa et al with sintering as compared to untreated scaffolds (0.7 MPa).…”
Section: Limitations and Future Prospectsmentioning
confidence: 99%
“…The surface characteristics of the scaffold material, such as its electrical characteristics, free energy, and hydrophilicity, play a decisive role in the adhesion of the seed cells because contact between the seed cells and the scaffold material takes place at the scaffold surface (Jakob et al, 2012;Nguyen et al, 2012). Research has demonstrated that high surface hydrophilicity of a scaffold material can effectively improve the adhesion of the seed cells (Tarafder et al, 2013). Here, the experimental results indicated that the surface hydrophilicity of the bone scaffold material with core-cladding structure improved considerably compared with the PLGA/β-TCP composite scaffold material.…”
Section: Discussionmentioning
confidence: 79%
“…One of the important benefits of this method is the powder bed support by itself for each successive layer. The fragility of the obtained parts is considered a drawback [81][82][83][84][85][86][87][88].…”
Section: D Printing (3dp)mentioning
confidence: 99%